The Influence Of Financial Distress, Sustainability Reporting, Earnings Management On Stock Return - Margaret Margaret (UNIVED Press, 2025)
This study aims to analyze the influence of financial distress on stock return, the influence of sustainability reporting on stock return, and the influence of earnings management on stock return. The population in the study is all companies in the banking sub-sector based on IDX data in 2023 with a total of 47 companies. Meanwhile, the research sample is 41 companies with purposive sampling techniques. A total of 123 research observations consisting of 41 companies during the 2021-2023 period. The study finds that financial distress and earnings management significantly affect stock return. While sustainability reporting does not have significant effect on stock return.